Efektivitas Kinerja Dinas Pemadam Kebakaran Kota Padang dalam Pencegahan Bahaya Kebakaran - Suci Rahmadhani; Zikri Alhadi (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2021)
This research was conducted at the Fire Department of Padang City which aims to determine the effectiveness of performance, the obstacles that become obstacles and identify solutions to overcome obstacles in achieving performance in accordance with the objectives, targets and vision and mission of the Fire Department.This study uses a qualitative method using purposive sampling. The data collection process is carried out through observation, interviews, and documentation studies, while the data validity testing technique uses source triangulation with data analysis such as data collection, data reduction, data presentation and drawing conclusions. The results of the research carried out were to explain the effectiveness of the performance of the Padang City Fire Service is not optimal, because there are still obstacles such as: due to lack of facilities and infrastructure for fire prevention and disaster prevention, funds for disaster management, and Human Resources (HR), it can be concluded that The effectiveness performance of the Padang City Fire Department has not been maximized in preventing fire hazards.